Considereaciones del Liderazgo Transformacional que Fortalecen Competencias de Formación de Administradores en Instituciones de Educación Superior en Boyacá (2019)
The purpose of this article is to establish the relationship that exists between leadership styles and the training competencies of administrators at the level of higher education institutions in the department of Boyacá; for this purpose, recognition of contributions is made from the administrative theories, then the topic of transformational leadership is deepened in order to intertwine its developments with specific competences for business administration. The type of research is documentary with a qualitative approach. After the analysis of the results, it can be concluded that the elements that the transformational leadership contributes to strengthen the competences of the administrators have to do with: charisma, integration and diversity.